2020
DOI: 10.1038/s41419-020-02808-z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG14 promotes hepatocellular carcinoma progression via H3K27 acetylation activated PABPC1 by PTEN signaling

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide. LncRNA small nucleolar RNA host gene 14 (SNHG14) functions as an oncogene in a variety of cancers. However, the role of SNHG14 in HCC remains elusive. The aim of this study is to unravel the functional role and regulatory mechanism of SNHG14 in HCC. A cohort of 40 HCC tumor tissues and paired adjacent normal tissues were collected. Histopathological changes were analyzed by hematoxylin and eosin and immunohistochemistry. qRT-PCR and west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 33 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…clari ed the carcinogenic role of the CCDC144NL-AS1/miR-143-3p/MAP3K7 axis in the progression of gastric cancer [24]. additionally, lots of lncRNAs can also regulate RNA-binding proteins to in uence cancer progression, including RMST [25], HCG22 [26] and SNHG14 [27]. Here, we identi ed and veri ed several interacting protein partners of GK-IT1, including CDK1, MAPK1 and PABPC1.…”
Section: Discussionmentioning
confidence: 85%
“…clari ed the carcinogenic role of the CCDC144NL-AS1/miR-143-3p/MAP3K7 axis in the progression of gastric cancer [24]. additionally, lots of lncRNAs can also regulate RNA-binding proteins to in uence cancer progression, including RMST [25], HCG22 [26] and SNHG14 [27]. Here, we identi ed and veri ed several interacting protein partners of GK-IT1, including CDK1, MAPK1 and PABPC1.…”
Section: Discussionmentioning
confidence: 85%
“…However, Zhang et al [40] suggested that SNHG14 was low-expressed in CRC tumor tissues and correlated with poor prognosis. Throughout various studies in cancer realm, we could conclude that SNHG14 functioned as an oncogenetic role during tumorigenesis, including endometrial cancer [41], diffuse large B cell lymphoma [42], ovarian cancer [43,44], pancreatic ductal adenocarcinoma [45], cervical cancer [46,47], osteosarcoma [48], hepatocellular carcinoma [49][50][51], lung cancer [52,53], retinoblastoma [54] and bladder cancer [55]. In our study, we only enrolled 30 CRC patients and all the cases were collected from the Second Affiliated Hospital of Nanjing Medical University (Nanjing, China), thereby the results may bias.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that lncRNAs are aberrantly expressed and serve as diagnostic and prognostic biomarkers in HCC (40)(41)(42). LncRNA DUXAP8, as an oncogene, is dysregulated in multiple tumors, such as bladder cancer ( 13), non-small-cell lung cancer (43) and ovarian cancer (44).…”
Section: Discussionmentioning
confidence: 99%